(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Chemotherapy-induced fatty liver disease (CIFLD) is a growing concern among cancer patients undergoing treatment. Sonographic assessment provides a non-invasive approach to evaluate hepatic changes due to chemotherapy. The aim of the study was to assess the prevalence and severity of fatty liver development following chemotherapy. Methods: This prospective observational study was conducted at Ibn Sina Hospital, Dhaka, Bangladesh, from January 2023 to December 2024. A total of 77 patients undergoing chemotherapy were evaluated using purposive sampling. Sonographic assessments were performed before and after chemotherapy to determine hepatic changes. Fatty liver was graded based on echogenicity, liver-kidney contrast, and vascular blurring. Data were analyzed using SPSS version 23.0. Results: Among 77 patients, 55 (71.4%) developed fatty liver on sonographic assessment. Among 55 patients, fatty liver was more common in patients receiving platinum-based chemotherapy 32( 71.1%). Elevated ALT (>40 U/ L) was observed in 41(74.5%) cases, and AST (>35 U/L) in 38(69.1%). Among 39 patient, longer chemotherapy duration (>6 cycles) increased fatty liver severity (29, 74.4%). Conclusion: Chemotherapy-induced fatty liver is frequently observed, especially in patients receiving platinumbased regimens. It is associated with elevated liver enzymes and prolonged chemotherapy duration. Regular liver monitoring and early interventions are essential to minimize hepatic toxicity and ensure better treatment outcomes for patients undergoing chemotherapy.